An Examination of Level and Direction of Effort and Job Performance - Katerberg, Ralph; Blau, Gary (Academy of Management Journal, 1983)
The degree to which effort level and direction of the effort were related to job performance was examined in a field setting. Both direction and effort level were found to be significant predictors of individual performance, and direction of behavior contributes uniquely to the prediction of performance.